Birthplace as a capital: migratory flow, labor opportunities, and social reproduction in Brazilian men elite futsal players' careers - Iuri Salim de Souza; Murilo dos Reis Morbi; Illgner Veber Garcia Alves; Christiano Streb Ricci; Christiano Streb Ricci; Christiano Streb Ricci; Renato Francisco Rodrigues Marques (Frontiers in Sociology)
IntroductionThis study investigated the association between social inequality and the sport labor career development opportunities in Brazil. We analyzed the interrelation of Brazilian men's elite futsal players' birthplaces, the clubs' locations, and the intra-national (domestic) migratory flow among regions and states within this country. Brazil is a Global South country with a high level of social inequality where futsal is a very popular sport, with one of the most relevant men's national leagues worldwide—the Liga Nacional de Futsal (LNF). This league commonly counts on around 20 clubs, all located in the South or Southeast regions of Brazil, which are socioeconomically wealthier and with a higher Human Development Index (HDI). The aims of this study were: (a) to analyze how men professional futsal players' migratory flow occurs in Brazil, considering and relating the athletes' birthplace and the clubs' location regions; (b) to investigate players' working period in the same club and the tendencies of instability/stability in job positions; (c) to analyze relations between the socioeconomic inequality in different Brazilian regions and the athletes' migratory flow.MethodsWith a quantitative research approach, we analyzed the birthplaces and migratory flow of LNF players between 2013 and 2022. Data discussion was based on Bourdieusian Reflexive Sociology. Results showed that: LNF clubs are located in Brazilian socioeconomic richest regions, with most players born there; a minority of athletes remained working in the same club for 3 years or more.Discussion and conclusionWe concluded that Brazilian men's elite futsal context reproduces socioeconomic inequalities through a very regionalized athletes' migratory flow, and provides unstable labor conditions to players, who remain for short periods joining the same club.